Antibody Therapy for Histoplasmosis - Nosanchuk, Joshua D.; Zancope-Oliveira, Rosely M.; Hamilton, Andrew J.; Guimaraes, Allan J. (Frontiers in Microbiology, 2012)
The endemic human pathogenic fungus Histoplasma capsulatum is a major fungal pathogen with a broad variety of clinical presentations, ranging from mild, focal pulmonary disease to life-threatening systemic infections. Although azoles, such as itraconazole and voriconazole, and amphotericin B have significant activity against H. capsulatum, about 1 in 10 patients hospitalized due to histoplasmosis die. Hence, new approaches for managing disease are being sought. Over the past 10 years, studies have demonstrated that monoclonal antibodies (mAbs) can modify the pathogenesis of histoplasmosis. Disease has been shown to be impacted by mAbs targeting either fungal cell surface proteins or host co-stimulatory molecules. This review will detail our current knowledge regarding the impact of antibody therapy on histoplasmosis.